Technological Approach to Lithic Artifacts from Yukon Territory - Morlan, Richard E. (Book collections on Project MUSE., 1973)
Describes a list of 26 classes of stone artifacts which appears to be suitable for uniform application to archaeological collection from the Yukon Territory.